China's Emerging Informatization Strategy - Hanna, Nagy K.; Qiang, Christine Zhen-Wei (2012)
The authors adopt a holistic framework of China's e-development (informatization), covering the enablers of the knowledge economy and the application of information and communication technology (ICT) to government, business, and society. They identify the challenges facing government, business, and rural informatization, the growing digital divide between rural and urban areas and the innovations pursued to bridge this divide. This holistic framework is then used to identify key gaps and weaknesses in each enabler as well as synergies and cross-cutting coordination issues that need to be managed to support ICT application priorities and achieve national development goals.